Analisis Penerapan SAK EMKM pada Usaha Mikro Kecil dan Menengah di Kec. Galang: Studi Kasus UMKM Mulia Maju Panglong - Lumban Aritonang; Hendra Harmain; Nurwani Nurwani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
The preparation of financial reports for UMKM Mulia Maju Panlong is in accordance with SAK EMKM and to identify any obstacles in preparing financial reports based on SAK EMKM for UMKM Mulia Maju Panglong. This research was conducted using qualitative methods with a descriptive approach and preparing financial reports based on SAK EMKM using primary and secondary data taken from Mulia Maju Panglong. Data collection techniques in this research used observation, interview and documentation techniques. Based on data analysis, the research results show that the preparation of financial reports made by Mulia Maju Panglong is not fully in accordance with the Financial Accounting Standards for Small and Medium Entities (SAK EMKM) and only adapts to the needs of the business without understanding the applicable standards. Mulia Maju Panglong in presenting incomplete financial reports according to those in SAK EMKM by only making two financial reports in the form of a financial position report and a simple profit and loss report. There are several obstacles faced by Mulia Maju Panglong MSMEs in preparing financial reports in accordance with the provisions of SAK EMKM, namely the lack of knowledge of MSME owners regarding SAK EMKM which applies in preparing financial reports, the lack of understanding of MSME owners regarding technology and information and the absence of an obligation for MSMEs to prepare financial reports according to SAK EMKM standards.